A203 ACTIVITY OF MBX-8025, A POTENT AND SELECTIVE PPAR-δ AGONIST, ON BIOCHEMICAL MARKERS OF CHOLESTASIS. (1st March 2018) - Steinberg, A; Choi, Y; McWherter, C A; Boudes, P F
Abstract: Background: MBX-8025 is a potent and selective PPAR-delta agonist that decreases LDL-Cholesterol in subjects with mixed dyslipidemia and subjects with homozygous familial hypercholesterolemia (HoFH). Aims: Herein, we describe the activity of MBX-8025 to decrease biochemical markers of cholestasis. Methods: Alkaline phosphatases (AP), gamma glutamyl transferase (GGT), and total bilirubin (TB) were measured in three clinical studies: a 3-week parallel groups, placebo-controlled study in healthy volunteers; an 8-week parallel groups, placebo- and atorvastatin-controlled study in mixed dyslipidemia; and a 12-week dose escalating, non-controlled study in HoFH. MBX-8025 was administered orally, daily, at doses of 50, 100 and 200 mg. None of the subjects had a medical diagnosis of cholestasis and AP levels were considered within the normal range. Results: Rapid onset (within 4 days) and consistent decreases in AP were observed in all three studies. Decreases were sustained during MBX-8025 treatment, reversible within a week upon discontinuation of MBX-8025, and AP values were not seen below the lower reference limit. The AP decrease was not consistently dose-dependent and was associated with a concomitant decrease in GGT of similar amplitude. Decreases (between -20% and -40%) in TB were also observed in healthy volunteers and patients with HoFH. Conclusions: MBX-8025 significantly decreases biochemical markers of cholestasis in three different populations. A recent study in primary biliary cholangitis (NCT02609048) confirmed that this activity was translated in patients with cholestasis and was associated with a decrease in bile acid synthesis. Funding Agencies: CymaBay Therapeutics